Clew-like N-doped multiwalled carbon nanotube aggregates derived from metal-organic complexes for lithium-sulfur batteries. (October 2017) - Zuo, Pengjian; Zhang, Han; He, Mengxue; Li, Qin; Ma, Yulin; Du, Chunyu; Cheng, Xinqun; Huo, Hua; Gao, Yunzhi; Yin, Geping
Abstract: Lithium-sulfur (Li-S) batteries are considered one of the most promising energy storage systems because of their high energy density and natural abundance of sulfur. However, the inferior cycle stability and low Coulombic efficiency mainly due to the dissolution of ploysulfides impede the practical application of Li-S batteries. Herein, a novel three-dimensional clew-like N-doped multiwalled carbon nanotube (MWCNT) structure is obtained by carbonizing a kind of Ni-based metal-organic complex. When developed as conductive sulfur-loading hosts for Li-S batteries, the interconnected open-ended MWCNT materials show outstanding properties on encapsulating sulfur and immobilizing polysulfide intermediates. Moreover, the porous graphitic carbon as a conductive matrix facilitates the electron transport and the reversible electrochemical reaction of active materials during cycling. Therefore, a good cycling stability for 1000 cycles with a low capacity decay rate of 0.053% per cycle and a high Coulombic efficiency up to nearly 100% at 0.2C are achieved for the three-dimensional clew-like N-doped MWCNT/sulfur cathode material for Li-S batteries. Graphical abstract: